Effects of Different Planting Densities of Solanum nigrum L. on the Growth and Cadmium Uptake of Young Grapevines - Yuanxiang Yang; Qinfeng Zheng; Jin Wang; Xiulan Lv; Dong Liang; Renyan Liao; Lijin Lin (Agronomy)
We determine the best planting density of Solanum nigrum L. when intercropping with young grapevines to decrease cadmium (Cd) uptake by young grapevines. The effects of different planting densities (plant spacing × row spacing, in centimeters, and designated as 40 × 80, 40 × 40, 20 × 40 and 20 × 20, respectively) of S. nigrum on the growth and Cd uptake of young grapevines were studied. The 40 × 80 and 40 × 40 treatments increased the biomass, photosynthetic pigment content and photosynthesis of young grapevines, while the 20 × 40 and 20 × 20 treatments decreased these traits compared with the monoculture. With increasing intercropping density, the antioxidant enzyme activity of both plant species increased. Intercropping with S. nigrum decreased the Cd content in young grapevines, and the 40 × 80, 40 × 40, 20 × 40 and 20 × 20 treatments decreased the shoot Cd content in young grapevines by 20.89%, 26.11%, 38.12% and 45.95%, respectively, compared with the monoculture. Additionally, increasing the intercropping density increased the Cd content and extraction of S. nigrum. Thus, intercropping young grapevine with S. nigrum can decrease Cd uptake in young grapevines while remediating soil Cd-contamination, and the most optimal treatment is 20 × 20 in this experiment.